Upaya Pemberdayaan Masyarakat Melalui Pusat Kegiatan Belajar Masyarakat (PKBM) Banti Indonesia di Kecamatan Grobogan - Churaina Ainal Qilbi; Retha Anjelitha (Fakultas Dakwah dan Ilmu Komunikasi, 2023)
Community empowerment is an effort to optimize the ability of a society or community to improve skills, understanding, attitudes, abilities and be able to utilize existing resources to create welfare and independence so that the community becomes more empowered in the economic, social and cultural fields. One form of effort in empowerment is through non-formal education. One example of non-formal education that organizes learning activities is PKBM (Community Learning Activity Center). The Community Learning Activity Center (PKBM) Bakti Indonesia is one of the PKBMs in Grobogan District. PKBM Bakti Indonesia has an activity program that includes equivalency education, PAUD, TPA, community reading parks, skills such as computer training, multimedia training, and PKW training (Entrepreneurial Skills Education). This study aims to determine community empowerment efforts through PKBM in Grobogan District. This research uses a qualitative approach with descriptive methods. Data collection was done by interview, observation, and documentation. The results of the study show the role of PKBM Bakti Indonesia in community empowerment efforts in Grobogan District. In the field of education, the community is empowered through non-formal education institutions. While in the economic field, the community is empowered through the utilization and development of natural and human resources through PKW (Entrepreneurial Skills Education). Keywords: Empowermen,; Community, Community Learning Center